PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA AUDIOVISUAL TERHADAP TINGKAT PENEGTAHUAN PENCEGAHAN STROKE PADA PENDERITA HIPERTENSI DI PUSKESMAS CIGUGUR TENGAH KOTA CIMAHI - C, Nurpitri M.; D, Ramadhan M.; T, Sumarni (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Hypertension is one of the dangerous cardiovascular health problems when sufferers do not control it properly because it can cause complications such as stroke. Increasing knowledge is one important way to recognize signs, symptoms, prevention and treatment. Research Objective: To determine the effect of health education with Audiovisual media on the level of knowledge of stroke prevention in hypertension sufferers at the Cigugur Tengah Health Center in Cimahi City. Method: This type of quantitative research is pre-experimental with a one group pretest posttest design. The sampling technique used accidental sampling with a sample of 65 research subjects with the Wilcoxon test. This study used a measuring instrument in the form of a questionnaire that refers to the National Stroke Association (2015) reference source. Results: The results of the study using the Wilcoxon test obtained a p-value <0.001 smaller than the alpha value (α = 0.05). Conclusion: There is an effect of health education with audiovisual media on the level of knowledge of stroke prevention in hypertension sufferers